Investigating the Role of Health Expenditure on Tuberculosis Incidence in Indonesia - Shela Ardhana; Estro Dariatno Sihaloho (Universitas Negeri Semarang, 2024)
Tuberculosis has remained a persistent Indonesia health problem. With multiple government and donor initiatives to eradicate TB and its detrimental effects on Indonesia's health outcomes, the incidence of TB in Indonesia is still worsening. This study aimed to investigate the impact of health expenditure on TB incidence in Indonesia, which is one of the countries with the highest TB incidences globally. The method used is (Autoregressive Distributed Lag) to employ short-run and long-run effects using time series data from Indonesia from 2000 to 2021. The Findings demonstrate a significant inverse relationship between health expenditures (both public and private) and the incidence of tuberculosis. Increased public spending on healthcare is associated with a lower incidence of TB, both in the short and long term. Similarly, private health spending significantly contributes to TB reduction, with effects observed both immediately and over the long run. Furthermore, other variables also affect TB incidence. Higher Gini coefficients and unemployment rates are associated with increased TB incidence, while higher rates of BCG immunization and greater public effectiveness are associated with lower TB incidence.